Patterns of Social Interaction in Inclusive Education Class 5: Empirical Study at UPT SPF SDN Mattoangin 1 - Suasan, Meilinda; Syarifuddin, S.; Hartini, H.; Elpisah, E. (Manunggal Halim Jaya, 2024)
This research explores the social interaction patterns of inclusion students in grade 5 of Mattoangin 1 Elementary School, focusing on their interactions with fellow inclusion students, normal students, and teachers. The research method used is a qualitative approach with data collection techniques through observation, interviews, and documentation. The results showed that: 1) There are associative social interactions among children with special needs such as cooperation, accommodation and assimilation. There is no competition dissociative social interaction but there is conflict dissociative social interaction. 2) There are associative social interactions between children with special needs and teachers such as cooperation, accommodation and assimilation. As for the dissociative social interactions between children with special needs and teachers, neither competition nor conflict was found. There are associative social interactions between children with special needs and normal children such as cooperation, accommodation and assimilation. As for dissociative social interactions between children with special needs and normal children, they rarely even occur, be it competition or opposition. The implication of this research is the importance of promoting an inclusive learning environment to improve inclusive students' participation and social experiences in basic education.